Comparison of Proteome Profiling of Two Sensitive and Resistant Field Iranian Isolates of Leishmania major to Glucantime® by 2- Dimensional Electrophoresis - ZAREAN, Mehdi (Iran J Parasitol, 2015)
BACKGROUND: In this study, two-dimensional gel electrophoresis (2-DE) method was applied to determine and compare the protein spots expressed in the two field isolates of Leishmania major and recovered from the patients who were clinically sensitive and resistant to Glucantime® treatment. METHODS: Leishmania parasites were isolated from the cutaneous lesions of two CL infected patients in Shiraz, south of Iran. The species of the two isolates were identified as L. major using Nested-PCR. Sensitivity (Sh-214S) and resistance (Sh-120R) of the two isolates to meglumine antimonite were checked by the standard in vitro assays. Both sensitive and resistant L. major isolates were harvested in RPMI 1640 medium. Protein extractions were performed using TCA/Acetone method and the protein spots were determined by a two-dimensional gel electrophoresis (2-DE). The gels were stained with silver nitrate and analyzed by Image Master 2D Melanie-6 software. RESULTS: About 2967 protein spots were detected. Overall, 89 protein spots represented considerable changes of expression in the resistant isolate of L. major compared to the sensitive isolate. Of these, 60 and 29 protein spots were up-and down regulated, respectively. In addition, 11 protein spots present in the resistant isolate were noticed to be absent in the sensitive isolate. CONCLUSION: A number of proteins showed significant changes of expression in the drug-resistant L. major; moreover, the roles of these proteins probably enhanced the parasite resistance to the drug and increased parasite survival in the cells.